Problem pewności w neokantyzmie Johannesa Volkelta - Kubalica, Tomasz (Folia Philosophica, 2018)
The paper is devoted to an analysis of the epistemology of Johannes Volkelt, its main arguments and the relation of Volkelt’s theory of certainty to Kant and other contemporary philosophers, such as Edmund Husserl. Volkelt’s problem of scepticism is closely related to the positivist principle, which aimed at limiting all knowledge to our individual sphere of representations. This principle in Kant’s Critique of Pure Reason means the unknowableness of the thing in itself. Volkelt seeks for answer to the question about the trans-subjective knowledge. He finds a basis for the certainty in the dispresuppositional theory of the transsubjective minimum. The acceptance of the trans-subjective minimum determines too the possibility of metaphysics.